2003
DOI: 10.1097/00004770-200309000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Passive Ultrasonic Activation of 2% Chlorhexidine or 5.25% Sodium Hypochlorite Irrigant on Residual Antimicrobial Activity in Root Canals

Abstract: Ninety-four single-canal roots were prepared using the step-down technique. Forty-two canals were irrigated with 2% chlorhexidine, 42 canals with 5.25% sodium hypochlorite (NaOCl), and 10 control canals with phosphate-buffered saline (PBS). The chlorhexidine and NaOCl groups were each then equally divided into a final irrigation group and a 1-min passive ultrasonic irrigation group. Canals were enlarged with a Parapost drill. The apical 3-5 mm was covered with nail polish. Canals were rinsed with PBS, dried, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 17 publications
1
60
1
15
Order By: Relevance
“…62 Chlorhexidine exhibits substantivity to dentin and consequently may present residual antimicrobial effects for days to weeks and help prevent root canal reinfection. 52,[63][64][65][66][67][68][69] This seems to be an important advantage over NaOCl. Nevertheless, one important disadvantage of chlorhexidine is that it lacks tissue-dissolving ability, which is one of the obvious benefits of NaOCl.…”
Section: Discussionmentioning
confidence: 99%
“…62 Chlorhexidine exhibits substantivity to dentin and consequently may present residual antimicrobial effects for days to weeks and help prevent root canal reinfection. 52,[63][64][65][66][67][68][69] This seems to be an important advantage over NaOCl. Nevertheless, one important disadvantage of chlorhexidine is that it lacks tissue-dissolving ability, which is one of the obvious benefits of NaOCl.…”
Section: Discussionmentioning
confidence: 99%
“…However, a trend of lower percentages of live cells within the biofilm was observed in dentin treated with 1.5% NaOCl, which may indicate a limited residual antibacterial effect. Previous studies have also suggested limited residual antibacterial properties of NaOCl (29,34). Few endodontic regeneration case reports have demonstrated successful root canal disinfection using irrigation solutions without supplementary inter-appointment medicaments (5,6).…”
Section: A3mentioning
confidence: 99%
“…56,[96][97][98][99][100][101] The positively-charged molecules of CHX can adsorb onto dentine and prevent microbial colonization on the dentine surface for some time beyond the actual medication period 101 -this may inhibit re-infection of the canal subsequent to treatment 98 during that time period. CHX is retained in root canal dentine in levels sufficient to exert antimicrobial effects for at least 12 weeks.…”
Section: Chlorhexidinementioning
confidence: 99%